Juvenile idiopathic arthritis-associated uveitis - Matej Krišto; Sandro Kukić; Sanja Perić (Liječnički vjesnik, 2023)
Juvenile idiopathic arthritis (JIA) is a rheumatic disease of unknown etiology that clinically presents by affecting one or more joints over a 6-week period. Uveitis is the most common extra-articular manifestation in children suffering from JIA. It is usually asymptomatic during the initial stages, and therefore screening for JIA-associated uveitis is crucial.